2020
DOI: 10.1097/adm.0000000000000793
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of the COVID-19 Shutdown on Gambling Patterns in Australia: Consideration of Problem Gambling and Psychological Distress

Abstract: Objectives: The COVID-19 pandemic reduced access to gambling and contributed to widespread psychological distress. Psychological distress is a known risk factor for problem gambling as it can motivate excessive gambling as a coping response. The availability of gambling is considered a factor in maintaining problems. This paper aimed to investigate the impact of the shutdown of gambling venues on Australians, particularly among those vulnerable to mental health problems and gambling disorder. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
46
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 26 publications
3
46
0
Order By: Relevance
“…No hypotheses were formulated in relation to the current study due to its exploratory nature. Findings about the relationships between pre-existing gambling problems, psychological distress, and changes in gambling behaviour during the initial shutdown are reported in a separate paper (Gainsbury et al, 2020). Overall, we found that most participants in our sample reduced their gambling, but those at moderate risk of gambling problems were more likely to report increased gambling during the shutdown.…”
Section: Introductionsupporting
confidence: 47%
“…No hypotheses were formulated in relation to the current study due to its exploratory nature. Findings about the relationships between pre-existing gambling problems, psychological distress, and changes in gambling behaviour during the initial shutdown are reported in a separate paper (Gainsbury et al, 2020). Overall, we found that most participants in our sample reduced their gambling, but those at moderate risk of gambling problems were more likely to report increased gambling during the shutdown.…”
Section: Introductionsupporting
confidence: 47%
“…A different analysis from the same setting, studying ecological data of gamblers' activity in gambling operators on the overall Swedish gambling market, demonstrated modest effects on gambling in Sweden during the pandemic, mainly indicating a decrease rather than the opposite [3]. In Australia, during the reduction of physical gambling opportunities, overall gambling did not demonstrate an increase, also not in the online setting, and individuals with the highest degree of gambling problems were not more likely to increase their gambling [18]. In contrast, a study carried out during physical COVID-19-related restrictions in Ontario, Canada, demonstrated some migration from land-based to online gambling, and a number of risk factors, such as anxiety, depression, being influenced to gamble due to COVID-19 and gambling under the influence of cannabis or alcohol were associated with high-risk gambling months into the pandemic in 2020 [4].…”
Section: Introductionmentioning
confidence: 95%
“…Scores could range between 0 and 270. Given the lack of validated measures of gambling frequency, these measures were developed based on our earlier work (Gainsbury et al, 2020 ). Overall gambling engagement was collected and computed in a similar manner, summing the recoded responses to the nine online gambling activities with those from eight items assessing land-based gambling engagement.…”
Section: Methodsmentioning
confidence: 99%
“…Research out of Australia and Sweden to date using primarily cross-sectional designs shows an overall decrease in gambling engagement in the early months of the COVID-19 pandemic. This has been shown when measured by proportion of the population gambling (Biddle, 2020 ), frequency of gambling engagement (Gainsbury et al, 2020 ; Håkansson, 2020b ; Lindner et al, 2020 ), and gambling taxation levels (Håkansson, 2020a ). On the other hand, in Australia, the pandemic has also been associated with worsening of some mental health concerns such as anxiety (Kendrick & Isaac, 2020 ).…”
Section: Introductionmentioning
confidence: 97%